Planning, Developing, and Marketing Successful Web Sites - Miletsky, Jason (Cengage Learning, Inc, 2002)
If you are an E-Commerce entrepreneur, this is the book that you'll want your technical staff to read before creating your Web Site. This book provides future developers and designers information on how to think about creating a successful Web Site. In terms of the physical site and its role in the overall success of the dot-com business, it urges readers to think about their business as a complex program that responds to the needs of the customer who contact it over the Web. Broken down into three sections, this comprehensive book covers the following areas: Planning and Analysis, Designing and Developing, and Marketing. Managing and Marketing a Successful Web Site is for the programmer or developer who is serious about exploring the nature of a successful Web Site